The Role of Biology Education in Efforts to Revitalize Human Intelligence in the Era of Disruption: A Human Nature Perspective - Wulandari, Susanti; Akmaliah, Puput Hikmatul; Mariyam, Ade Siti; Yanawati, Riska (UIN Syekh Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
The impact of technological domination can threaten the balance of human natural intelligence. The aim of this research is to analyze how biology education can be a solution in overcoming these challenges. The research method used involved an in-depth literature review of the concepts of natural intelligence, human nature, and the impact of technology on both. In addition, field research was conducted to analyze the effectiveness of biology education strategies implemented in several educational institutions. The research results show that biology education, critical thinking skills, and connection with nature can make a significant contribution to revitalizing human intelligence. The integration of biological concepts allows individuals to stay connected and offset the negative effects of technology. Thus, biology education has a crucial role in maintaining human natural intelligence in an era of disruption.